An observational cohort study of the use of five-grass-pollen extract sublingual immunotherapy during the 2015 pollen season in France - Patrick Blin (Allergy, Asthma & Clinical Immunology, 2018)
Abstract Background Allergic rhinitis affects around one quarter of the Western European population. Prophylactic allergen immunotherapy may be useful to reduce the risk of acute symptomatic attacks (hayfever). A five-grass pollen extract sublingual immunotherapy (5GPE-SLIT) has been developed for the treatment of allergic rhinitis to grass pollen. The objective of this study was to describe real-world treatment patterns with 5GPE-SLIT in France with respect to the prescribing information. Methods This prospective cohort study was conducted by 90 community and hospital allergists. Adults and children (> 5 years old) starting a first treatment with 5GPE-SLIT prior to the 2015 pollen season were eligible. Data was collected at the inclusion visit and at the end of the pollen season. The primary outcome variable was compatibility of 5GPE-SLIT prescription with the prescribing information. This was determined with respect to four variables: (1) interval between 5GPE-SLIT initiation and onset of the pollen season ≥ 3 months, (2) age of patient ≥ 5 years, (3) intermittent symptoms or mild symptom severity (4) confirmatory diagnostic test. At study end, symptoms reported during the pollen season and any modifications to treatment or adverse events were documented. Results 280 adults and 203 children were enrolled. The prescribing information was respected for 82.5% of adults and 86.7% of children. A skin test was performed for all patients. 5GPE-SLIT was started 3–5 months before the pollen season for 85.3%. Treatment was discontinued before the start of the pollen season in 11.0% of patients overall, generally because of an adverse event (78.8% of discontinuations). The mean duration of treatment was 5.2 months in adults and 5.6 months in children. At the end of follow-up, symptoms during the pollen season were intermittent for 75.0% of adults and 85.7% of children, and severity was mild for 61.8 and 66.0% respectively. During 5GPE-SLIT, the following symptoms reported during the previous year were not reported again in > 50% of patients: nasal congestion, rhinorrhoea, repeated sneezing, conjunctivitis and nasal pruritus. Conclusions 5GPE-SLIT use was generally consistent with prescribing recommendations and was associated with an improvement of AR severity, with resolution of the principal AR symptoms in around half the patients treated. Trial registration EUPAS9358. Registered 13 May 2015. Not prospectively registered. http://www.encepp.eu/encepp/viewResource.htm?id=16229